Electrochemical fixation of CO2 to organohalides in room-temperature ionic liquids under supercritical CO2. (10th April 2015) - Tateno, Hiroyuki; Nakabayashi, Koji; Kashiwagi, Tsuneo; Senboku, Hisanori; Atobe, Mahito
Graphical abstract: Highlights: The electrochemical properties of novel reaction media such as ionic liquid (IL)/supercriticalCO2 (scCO2 ) systems were evaluated. The IL/scCO2 systems were applied as reaction media for the electrochemical carboxylationof various organohalides. The IL/scCO2 systems were determined as useful media for the electrochemicalcarboxylation. The current efficiencies obtained for the IL/scCO2 systems were much higher than thoseobtained in ILs under subcritical CO2 conditions. Abstract: The electrochemical properties of novel reaction media, ionic liquid (IL)/supercritical CO2 (scCO2 ) systems, were evaluated and the electrochemical carboxylation of various organohalides in these systems was demonstrated. Voltammetric studies revealed that the CO2 solubility in an IL such as N, N -diethyl- N -methyl- N -(2-methoxyethyl) ammonium bis(trifluoromethanesulfonyl) imide ([DEME][TFSI]) increased in the presence of scCO2 . The IL/scCO2 systems were found to be effective for the electrochemical carboxylation of various organohalides.